Recursos didácticos para el desarrollo de competencias comunicacionales en octavo grado, de la Escuela de Educación Básica 18 de Noviembre, Loja 2024. - Bustamante, Miriam Jackeline (2024)
This research concentrates on the significance and effectiveness of educational materials in fostering students' communication skills. The main aim of this study was to assess the influence of educational resources through a teaching proposal designed to improve communication skills in eighth-grade students at Escuela de Educación Básica 18 de Noviembre, Loja 2024. Three specific goals were outlined: First, to assess the communication skills students have acquired during their learning process; second, to create a teaching proposal based on educational resources to enhance students' communication skills; and third, to assess the teaching proposal based on educational resources for developing students' communication skills. The methodology involves a mixed approach, incorporating qualitative and quantitative methods. Surveys were administered to students and teachers, in addition to classroom observations and examination of the educational materials utilized. The collected data facilitated the evaluation of the impact of various educational resources, such as audiovisual materials, interactive activities, educational games, and digital tools, in promoting communication skills. The research results show that integrating diverse and modern educational resources improves students' oral and written comprehension and expression and increases their motivation and participation in class. The importance of ongoing teacher training in using new technologies and teaching methods and the need to update and diversify educational materials is highlighted. The study concludes that implementing appropriate educational resources is essential for developing communicative competencies in eighth-grade students. This research provides a solid foundation for future initiatives and educational policies aimed at improving education quality and students' comprehensive development.